Oratório Messias de Georg Friedrich Händel - Pereira, Davi Lopes (2018)
This dissertation presents a study proposal on the oratory genre, with Händel as one of its main composers and its practice in the Baroque period in England, especially in the city of London. The purpose of this dissertation is to present the circumstances that involved the composition of the Messiah Oratory and to explain how these circumstances influenced it. We are based in an intense research work consulting several bibliographical sources and versions of the oratory, whose objective was to present an opinion based on authors that are referential in the subject. We present succinctly the phases of Händel's life, trying to show the main facts and how they influenced him in the composition of the Messiah. We also clearly portray the pretensions of Charles Jennens in his selection of the text for the Oratory. We include in the appendix the first part of the Messiah that will help in understanding the dissertation presented here, corroborating the truth of the facts presented in it. Finally, we conclude at the end of the dissertation that the Messiah Oratory is the best known of humanity, making its presentation a tradition at Easter, Christmas and other events that so require. With this, he became a patrimony of humanity for those who enjoy classical music.